Rotoresect for bloodless transurethral resection of the prostate: a 4-year follow-up - Michel, Maurice Stephan; Knoll, Thomas; Trojan, Lutz; Köhrmann, Kai-Uwe; Alken, Peter (BJU international, 2003)
OBJECTIVE To report the results and long-term follow-up of transurethral resection of the prostate (TURP) with a new resection device, the Rotoresect (Karl Storz, Tuttlingen, Germany). PATIENTS AND METHODS Most endoscopic resection techniques for benign prostatic tissue aim for high ablation rates and minimal bleeding. Available resection electrodes are effective, but cause high blood loss (loop electrode), or less bleeding but poorer ablation rates (electrovaporization). To resolve these conflicts the Rotoresect was developed in 1995; it consists of a specially designed rotating resection electrode, driven by a micromotor, and a high-frequency current to enable simultaneous coagulation, vaporization and mechanical tissue removal during resection. To date, 84 patients with benign prostatic hyperplasia have had their prostate resected with this device (mean prostate size 46.0, sd 18.4 mL) and have been assessed for up to 4 years. RESULTS During resection there was very little bleeding, with no significant changes in haemoglobin or sodium levels. The mean (sd) duration of catheterization was 1.4 (1.1) days; the urinary peak flow rate was improved from 9.7 (3.2) to 24.2 (8.23) mL/s and the residual urine volume reduced from 187.3 (109.6) to 22.7 (19.5) mL. The International Prostate Symptom Score and quality-of-life index were both improved, from 24.0 (7.5) to 4.1 (2.7), and 4.2 (3.2) to 0.8 (0.9), respectively. Overall the results were stable during the 4 years of follow-up. CONCLUSION The Rotoresect combines the advantages of standard resection (high ablation rate) by actively rotating the resection electrode, and the haemostatic effect of electrovaporization (minimal blood loss) by simultaneous tissue coagulation and vaporization.